Historiography by Proxy: A Eurocentric View of Arabic Translation History through the Eyes of an Orientalist - Al-Batineh, Mohammed (Dirasat: Human and Social Sciences, 2019)
The present paper discusses the impact of Eurocentrism and ideology on translation historiography. It mainly focuses on the Western discourse on Arabic translation history by analysing the discourse of De Lacy Evans O'Leary, an English historian and orientalist, in two of his works documenting the Arabic translation history during the Islamic Golden Age (8th—14th century). During that period, there were two translation movements: the first movement involved translating Greek works into Arabic, while the second involved the translation wave from Arabic into Latin and Hebrew. The paper hypothesizes that O'Leary’s view exhibits a Eurocentric view manifested in highlight the first translation movement while placing a minimal emphasis on the second. The study makes use of corpus analysis to qualitatively and quantitatively analyse O'Leary’s discourse in two of his books. The quantitative analysis relied on frequency lists while the qualitative analysis made use of concordance function in WordSmith (Scott, 2010). The results revealed that O'Leary’s discourse presented a Eurocentric view highlighting first translation movement, while ignoring the role Arabs played, through the medium of translation, in preserving Greek knowledge and passing it later to the West.